Isolation of urease-positive Vibrio parahaemolyticus from diarrheal patients in Northeast Brazi - Magalhães, Marcelo; Magalhães, Vera; Antas, Maria G.; Tateno, Seiki (Revista do Instituto de Medicina Tropical de São Paulo, 1991)
Of 21 human fecal strains of Vibrio parahaemolyticus, isolated on the Northeast Coast of Brazil, eight (38%) were urease positive. Most of these strains, in contrast to the urease-negative ones, did not produce the hemolysin responsible for the Kanagawa phenomenon.